2016
DOI: 10.3389/fmicb.2016.01582
|View full text |Cite
|
Sign up to set email alerts
|

Use of Direct LAMP Screening of Broiler Fecal Samples for Campylobacter jejuni and Campylobacter coli in the Positive Flock Identification Strategy

Abstract: Rapid identification of Campylobacter-positive flocks before slaughter, following freezing and heat treatment for the Campylobacter-positive carcasses at the slaughterhouses is an effective control strategy against foodborne campylobacteriosis. We evaluated a loop-mediated isothermal amplification (LAMP) assay for the direct screening of naturally contaminated chicken cloacal swabs for C. jejuni/C. coli to compare this assay with conventional quantitative culture methods. In a comparison study of 165 broilers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…A recent publication ( Sabike et al, 2016 ) reported the use of Campylobacter LAMP assay for direct detection in chicken fecal samples. They achieved detection of 3.89 and 3.60 log cfu × g −1 of fecal sample for C. jejuni and C. coli , respectively, in artificially contaminated fecal samples, and a three-step DNA precipitation protocol was used to improve sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent publication ( Sabike et al, 2016 ) reported the use of Campylobacter LAMP assay for direct detection in chicken fecal samples. They achieved detection of 3.89 and 3.60 log cfu × g −1 of fecal sample for C. jejuni and C. coli , respectively, in artificially contaminated fecal samples, and a three-step DNA precipitation protocol was used to improve sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“… Sabike et al (2016) reported that their analysis of naturally contaminated specimens from one particular farm showed a high frequency of false negative results for Campylobacter loadings ranging from <3 to 5.81 log cfu × g −1 . The authors discussed that this high rate of false negatives may be explained by inhibitors of DNA amplification, possibly derived from substances in the poultry feeding stuffs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMP was developed for the detection of Campylobacter spp. in poultry samples such as meat, carcass swabs, and fecal samples (Yamazaki et al, 2008, 2009b; Sabike et al, 2016; Romero and Cook, 2018; Sabike and Yamazaki, 2019). To study the epidemiology of Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, to detect the presence of the Campylobacter spp. in cloacal swabs, ceca, meat and environmental cleaning samples, an enrichment step of 22 to 24 h is needed (Yamazaki et al, 2009b; Sabike et al, 2016; Sabike and Yamazaki, 2019). Consequently, it takes a total of at least 24–26 h for sample enrichment, preparation, amplification, and detection.…”
Section: Introductionmentioning
confidence: 99%